Investigating Biomarkers for COVID-19 Morbidity and Mortality - Ceci, Flavio M.; Ferraguti, Giampiero; Lucarelli, Marco; Angeloni, Antonio; Bonci, Enea; Petrella, Carla; Francati, Silvia; Barbato, Christian; Di Certo, Maria Grazia; Gabanella, Francesca; Gavaruzzi, Francesca; Mastroianni, Claudio Maria; et al. (Current Topics in Medicinal Chemistry, 2023)
Background and Objectives: This retrospective study aims to disclose further early parameters of COVID-19 morbidity and mortality. Methods: Three hundred and eighty-two COVID-19 patients, recruited between March and April 2020, were divided into three groups according to their outcome: (1) hospital ward group (patients who entered the hospital wards and survived); (2) intensive care unit (ICU) group (patients who attended the ICU and survived); (3) the deceased group (patients admitted to ICU with a fatal outcome). We investigated routine laboratory parameters such as albumin, glycemia, hemoglobin amylase, lipase, AST, ALT, GGT, LDH, CK, MGB, TnT-hs, IL-6, ferritin, CRP, PCT, WBC, RBC, PLT, PT, INR, APTT, FBG, and D-dimer. Blood withdrawal was carried out at the beginning of the hospitalization period. Results: ANOVA and ROC data evidenced that the concomitant presence of alterations in albumin, lipase, AST, ALT, LDH, MGB, CK, IL-6, ferritin in women, CRP and D-dimer is an early sign of fatal outcomes. Conclusion: The present study confirms and extends the validity of routine laboratory biomarkers (i.e., lipase, AST, ALT, LDH, CK, IL-6, ferritin in women, CRP and D-dimer) as indicators of COVID-19 morbidity and mortality. Furthermore, the investigation suggests that both gross changes in albumin and MGB, markers of liver and heart damage, may early disclose COVID-19 fatal outcomes.
Keywords: SARS-CoV-2